Investigation of the Patterns of Changes in the Structural Strength of Moistened Loess Soils Under Dynamic (Seismic) Influences - Khakimov Gayrat Akramovich; Baymatov Shaxriddin Xushvaqtovich; Rakhimov Sherzod Abduvakhobjonovich; Tulyaganov Zafar Sunnatovich; Adilkhanova Zarofatkhan (Scientific Trends, 2024)
This scientific article presents the results of laboratory and field experimental studies on the study of patterns of changes in the structural strengths of moistened loess soils under dynamic influences, depending on various external and internal factors. Recommendations have been developed for determining the design pressure based on buildings, taking into account changes in the strength characteristics of loess soils under seismic influences.
Keywords: adhesion; connectivity; vibration compaction; angle of internal friction; bulk soil; loess soil; strength characteristics; vibration roller; structural strength; method; seismic subsidence.